Inducible IFN-γ Expression for MHC-I Upregulation in Devil Facial Tumor Cells - Ong, Chrissie E. B.; Lyons, Alan Bruce; Woods, Gregory M.; Flies, Andrew S. (Frontiers in Immunology, 2019)
The Tasmanian devil facial tumor (DFT) disease has led to an 80% reduction in the wild Tasmanian devil (Sarcophilus harrisii) population since 1996. The limited genetic diversity of wild devils and the lack of MHC-I expression on devil facial tumor cells have been implicated in the lack of immunity against the original DFT clonal cell line (DFT1). Recently, a second transmissible tumor of independent origin (DFT2) was discovered. Surprisingly, DFT2 cells do express MHC-I, but DFT2 cells appear to be on a trajectory for reduced MHC-I expression in vivo. Thus, much of the ongoing vaccine-development efforts and conservation plans have focused on MHC-I. A major limitation in conservation efforts is the lack of species-specific tools to understand Tasmanian devil gene function and immunology. To help fill this gap, we developed an all-in-one Tet-Off vector system to regulate expression of IFN-γ in DFT cells (DFT1.Tet/IFN-γ). IFN-γ can have negative effects on cell proliferation and viability; thus, doxycycline was used to suppress IFN-γ production whilst DFT1.Tet/IFN-γ cells were expanded in cell culture. Induction of IFN-γ following removal of doxycycline led to upregulation of MHC-I but also the inhibitory checkpoint molecule PD-L1. Additionally, DFT1.Tet/IFN-γ cells were capable of stimulating MHC-I upregulation on bystander wild type DFT cells in co-culture assays in vitro. This system represents a major step forward in DFT disease immunotherapy and vaccine development efforts, and ability to understand gene function in devils. Importantly, the techniques are readily transferable for testing gene function in DFT2 cells and other non-traditional species.